Pictorial Quiz - Fatima Iqbal; Muhammad Jamaluddin (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
My patient 30 years of age G3P2 with 30 weeks of gestational amenorrhea came with complain of abdominal distension, relative constipation and multiple episodes of vomitings for 3 days. She had history of eating hairs for 3 years. On examination, abdomen was distended and tense overall. Gutsounds inaudible. Digital rectal examination was unremarkable. X-ray Erect abdomen showed multiple air fluid levels. Attached below is the picture of operative finding.